Economic decision-making systems in critical times: The case of ‘Bolsa Familia’ in Brazil - Pereira Junior, Alfredo [UNESP] (2022)
Kahneman's theory of two systems assumes that human decision making in Economy is based on two cognitive systems, one that is automatic, intuitive and mostly unconscious, and one that is reflexive, rational and fully conscious. The authors consider Kahneman’s approach incomplete and limited in accounting for the creativity of embodied agents grasping the opportunities afforded by physical and social environments. This limitation leads us to argue for the existence of a third system in decision making in Economy, the creative intuition based on direct perception of affordances, addressing not only the dispositions and goals of agents but also the social and environmental responsibility of corporations and governments. The authors argue that the third decision-making system the authors propose implies a concept of intuition that is different from the type of association process discussed by Morewedge and Kahneman [2] and gives an example of the third system operation, the Bolsa Família in Brazil, and finding new options for the funding of similar programs.